Relationship between Cardiorespiratory Fitness and Quality of Life in the Elderly - Qomariyah Qomariyah; Farid Rahman (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: The aging process occurs so fast, therefore the quality of life of the elderly needs to be very concerned. Cardiorespiratory fitness is one of the predictor factors to improve the quality of life in the elderly. The study aims to find out whether there is a relationship between cardiorespiratory fitness and the quality of life of the elderly.Subjects and Method: This was a cross-sectional study conducted in Dukuh Pepe, Kwarasan, Juwiring, Klaten, Central Java. A sample of 31 elderly (aged 50-70 years) was selected using the purposive sampling method. The dependent variable was quality of life. The independent variable was cardiorespiratory fitness. Quality of life was measured by Ina's whoqol-breff questionnaire. Cardiorespiratory fitness was measured by a six-minute walking test. The data were analyzed with the spearman correlation test and the simple linear regression test.Results: Cardiorespiratory fitness improved the quality of life in the elderly in the physical health domain (OR= 44.55; 95% CI= 20.49 to 68.62), psychological domain (OR= 51. 14; 95% CI= 26.10 to 76.19), personal relationship domain, (OR= 76.94; 95% CI= 52.57 to 101.30), environmental domain (OR= 78.92; 95% CI= 49.51 to 108.33) although it was statistically insignificant.Conclusion: There was no relationship between cardiorespiratory fitness and the quality of life of the elderly in rural areas in the aspects of the physical health domain, the psychological domain, the personal relationship domain, and the environmental domain.Keywords: cardiorespiratory fitness, quality of life, elderly, six-minute walking test, whoqol-breff.Correspondence: Farid Rahman. Physiotherapy Study Program, Faculty of Health Sciences, Universitas Muhammadiyah Surakarta. Jl. Ahmad Yani, Pabelan, Kartasura, Surakarta, Central Java 57162, Indonesia. Email: Fr280@ums.ac.id. Mobile: 085223333141.Indonesian Journal of Medicine (2022), 07(04): 371-378https://doi.org/10.26911/theijmed.2022.07.04.02